OBTAINING THE RECOMBINANT ORF3 PROTEIN OF HEPATITIS E GENOTYPE 3 AND EVALUATION OF ITS ANTIGENIC PROPERTIES - G. I. Alatortseva; A. V. Sidorov; L. N. Nesterenko; L. N. Luhverchik; A. V. Milovanova; Yu. I. Ammur; M. I. Mikhailov; K. K. Kyuregyan; S. V. Zhavoronok; V. V. Zverev (Журнал микробиологии, эпидемиологии и иммунобиологии, 2018)
Aim. Design аис1 construction of the hepatitis E virus (HEV) genotype 3 full-size ORF3 recombimnt polypeptide. Materials and methods. Escherichia coli strains, ptasmid vectors, serologiral and biological amples, molecular biological, bioinformatic, biotechnological, biochemical and serological methods.Results. RNA was isolated from pig fecal extracts collected on Belgorod farms and was used in RT-PCR to obtain the fragment of the orf3 gene of the hepatitis E virus genotype 3. Using A/T-cloning a recombinant plasmid was obtained with insertion of a DNA fragment (230 bp) encoding the N-terminal region of the ORF3 protein. The primary structure of the missing C-terminal region of the ORF3 VGE of the genotype 3 was calculated by bioinformatics methods. Codon optimization of the sequence for biosynthesis in E.coli cells was performed. For constructing the recombinant plasmid a chemically synthesized DNA fragment encoding the fulllength ORF3 protein had been used. E.coli strain producing full-size recombinant protein ORF3 fused to E.coli beta-galactosidase was developed. Recombinant protein ORF3 had been isolated from the inclusion bodies of the E.coli biomass and purified by size exclusion chromatography. Antigenic specificity of recombinant polypeptide had been confirmed in immunochemical reactions (ELISA, Western blot) with sera from patients with hepatitis E and control groups of patients. Conclusion. HEV genotype 3 ORF3 recombinant antigen had been designed, and itfs applicability in diagnostic tests had been experimentally confirmed.